OP0007 MRI of the wrist and finger joints in inflammatory joint diseases at one year interval. MRI features to predict bone erosions. (1st June 2001) - Savnik, A; Malmskov, H; Thomsen, HS; Graff, LB; Nielsen, H; Bliddal, H
Abstract : Background: Magnetic resonance imaging (MRI) has important applications in inflammatory joint diseases since it allows a direct visualisation of both bony and soft tissue. The wrist and finger joints are first affected in rheumatoid arthritis and of prime interest in predictive studies. Bone oedema is important MRI feature in inflammatory joint diseases and it has been suggested to be a forerunner of bone erosion. Objectives: To compare the ability of the outlined synovial volumes before and after Gadodiamide injection, presence of bone marrow oedema, bone erosions and enhancement after Gadodiamide injection to predict progressions in bone erosions after 1 year follow up in patients with different types of inflammatory joint diseases. Methods: 84 patients underwent MRI, laboratory and clinical examination at baseline and 1 year later. MRI of the wrist and finger joints was performed in 22 patients with rheumatoid arthritis less than 3 years (group 1), 18 patients with spondylarthropathies (group 2), 22 patients with more than 3 years duration of rheumatoid arthritis (group 3) and 20 patients with arthralgia (group 4). Results: The total outlined synovial volumes in the finger joints before Gadodiamide injection and the number of bone erosions at baseline MRI were highly predictive of bone erosions one year later in patients with rheumatoid arthritis (group 1 and 3). The number of bones with erosions and oedema varied significantly between the patient groups. The strongest individual predictor of bone erosions at one year follow up was bone marrow oedema, if present at the wrist at baseline. Bone erosions on baseline MRI were in few cases reversible at follow up MRI. Conclusion: The total synovial volume in the finger joints before contrast, the number of bone erosions and presence of bone oedema in the wrist at baseline seems to be predictive for the number of bone erosions 1 year later and may be used in screening. The importance of very early bone changes on MRI and the importance of these findings reversibility remain to be clarified. References: Ostergaard M, Gideon P, Henriksen O, Lorenzen I. Synovial volume-a marker of disease severity in rheumatoid arthritis? Quantification by MRI. Scand J Rheumatol. 1994;23:197–202 McQueen FM. Magnetic resonance imaging in early inflammatory arthritis: what is its role? Rheumatology 2000;39:700–706 McGonagle D, Gibbon W, O'Connor P, Green M, Pease C, Ridgway J, Emery P. An anatomical explanation for good-prognosis rheumatoid arthritis. Lancet 1999;353:123–4